Temple de Liber Pater ou Capitole ? - Khaled Marmouri (Antiquités Africaines, 2017)
The traditional identification of Liber Pater as the titular divinity worshipped at the major sanctuary on the north-west side of the old forum of Lepcis Magna is nowadays deeply contested. Some scholars now identify that temple as a Capitolium. Nevertheless, most studies have been based on incomplete documentation relating to the sanctuary. Our study attempts to record and examine all the material, with a specific insistence on religious dedications. The texts are here revised and briefly discussed, allowing us to draw out different epigraphic and iconographic indications, which prevent us, as yet, from giving up the conventional thesis of a dedication of the sanctuary to the worship of Liber Pater.